2002
DOI: 10.1038/sj.bjc.6600468
|View full text |Cite
|
Sign up to set email alerts
|

Lymphadenectomy and adjuvant therapy in endometrial carcinoma: role of adjuvant chemotherapy

Abstract: To evaluate the therapeutic benefit of lymphadenectomy and adjuvant therapy, in particular chemotherapy, we retrospectively analysed survival rates and patterns of recurrence of endometrioid adenocarcinoma in 106 patients who underwent surgery including retroperitoneal lymphadenectomy. Adjuvant chemotherapy was administered to 46 patients (42 received a platinumbased regimen) and pelvic irradiation to 12. The 5-year survival rate of 23 patients with lymph node metastasis was worse than that of patients without… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 24 publications
0
9
0
1
Order By: Relevance
“…Prior studies have shown a wide variation in survival based on lymph node location. In several series patients with involvement of pelvic lymph nodes only had nonsignificant differences in survival compared with those with positive paraaortic lymph nodes ( McMeekin et al , 2001 ; Mariani et al , 2002 ; Otsuka et al , 2002 ; Havrilesky et al , 2005 ; Hoekstra et al , 2009 ; Lewin et al , 2010 ; Todo et al , 2011 ). In other series better survival was noted for patients with pelvic nodes ( Morrow et al , 1991 ; Hirahatake et al , 1997 ; Yokoyama et al , 1997 ; Watari et al , 2005 ; Fujimoto et al , 2007 ; Karube et al , 2010 ; Lewin et al , 2010 ).…”
Section: Discussionmentioning
confidence: 98%
“…Prior studies have shown a wide variation in survival based on lymph node location. In several series patients with involvement of pelvic lymph nodes only had nonsignificant differences in survival compared with those with positive paraaortic lymph nodes ( McMeekin et al , 2001 ; Mariani et al , 2002 ; Otsuka et al , 2002 ; Havrilesky et al , 2005 ; Hoekstra et al , 2009 ; Lewin et al , 2010 ; Todo et al , 2011 ). In other series better survival was noted for patients with pelvic nodes ( Morrow et al , 1991 ; Hirahatake et al , 1997 ; Yokoyama et al , 1997 ; Watari et al , 2005 ; Fujimoto et al , 2007 ; Karube et al , 2010 ; Lewin et al , 2010 ).…”
Section: Discussionmentioning
confidence: 98%
“…23 Some authors in Japan evaluated the therapeutic benefit of lymphadenectomy and adjuvant chemotherapy in node-positive endometrioid EC patients and grade 3 EC patients. 8,24 They suggested that disease recurrence occurs predominantly outside the pelvis and chemotherapy may be a suitable choice for adjuvant therapy in EC patients following systematic lymphadenectomy. Given the results of these trials, we suggest adjuvant chemotherapy following systematic lymphadenectomy in FIGO stage IIIC and IV endometroid EC patients presenting primarily as nodal spreads.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, pelvic radiotherapy did not appear to be effective in reducing extrapelvic recurrence. 8 Also, pelvic radiotherapy frequently causes gastrointestinal complications including small bowel obstruction after para-aortic lymphadenectomy. 28,29 If appropriate chemotherapy is given after complete lymphadenectomy in patients with LN metastasis, pelvic radiotherapy could be reserved for possible pelvic recurrence in the future.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Otsuka [35] utilise un argument classique mais discutable pour justifier la cytoréduction : le pronostic des cas N+ macroscopiques rejoint après curage ganglionnaire « théra-peutique » celui des N+ microscopiques. Indépendamment de cet argument, on sait que l'irradiation externe est mal adaptée au contrôle des adénomégalies.…”
Section: Valeur Thérapeutique Du Curage Ganglionnaire En Présence D'uunclassified